PENGARUH KREDIBILITAS MEREK, PERCEIVED QUALITY, DAN DIGITAL MARKETING TERHADAP MINAT BELI PRODUK THE ORIGINOTE DI KOTA BATAM - Anggraini, Nur Afni; Wasiman (LPPM Universitas Putera Batam, 2025)
This study examines the influence of brand credibility, perceived quality, and digital marketing on purchase intention of The Originote skincare products in Batam City. Using quantitative approach with 100 respondents and multiple linear regression analysis, the results show that perceived quality (p < 0.001) and digital marketing (p = 0.001) significantly influence purchase intention, while brand credibility does not (p = 0.178). Simultaneously, all three variables explain 78.2% of purchase intention variance (F = 119.389, p < 0.001). The findings indicate that perceived quality and digital marketing strategies are more crucial than brand credibility in driving consumer purchase intentions for skincare products. Keywords: brand credibility; digital marketing; perceived quality; purchase intention; skincare products.